Profesor, mistrz, przyjaciel, kolega - o dedykacjach poświęconych Profesorowi Piotrowi Żbikowskiemu - Krauz, Maria (Słowo. Studia językoznawcze, 2014)
The author of the article studies handwritten dedications addressed to Professor Piotr Żbikowski – a scholar, prominent researcher of literature, working many year at the University of Rzeszow. She analyzes the construction of short texts whose designated by the verb dedicate: someone dedicates something to someone, examines both conventional acts as and individual, original formulas, containing allusions and phrases understandable only to the recipient. From the description of the language emerges a picture of a scholar, master and friend, which value knowledge and tradition.